EFEKTIFITAS DAN EFISIENSI PEMANFAATAN DANA BANTUAN OPERASIONAL KESEHATAN DENGAN PENERAPAN METODE ANALYTIC HIERARCHY PROCESS - Kasman Makkasau (Center for Health Policy and Management, 2012)
Background: Millennium Development Goals (MDGs) is a globalcommitment that must be realized by all countries by 2015,to accelerate the goal then the health ministries of BantuanOperasional Kesehatan (BOK) in helping the distric implementappropriate health services by improving the performance ofSPM Puskesmas and networks as well as Upaya KesehatanBersumber Masyarakat (UKBM) in carrying out preventive andpromotive health services. Utilization of funds is an authorityof the BOK clinic, it is necessary for an effective method indetermining program priorities. Along with the progress of scienceand technology in the field of public health and medicine,has provided a wide range of alternatives that can be used tosolve the health problems that occur in the community today.Objective: to determine the utilization of funds BOK interventionis most effective, with metodogi analitic using a modelsystem of decision makers using AHP.Methods: Analytic Hierarchy Process (AHP) is a model approachthat provides an opportunity for planners and programmanagers in health to be able to build the ideas or the ideasand define problems that exist in a way to make assumptionsand then get the desired solution.Results: Based on the analysis by using the AHP model, it canproduce an alternative to the use of program funds BOK highlyeffective in community health centers. By using the AHP modelthen any program that will be implemented with clearly definedpriorities, compared to using Hanlon, Delbeq and PEARL whichhas been used by the manager of health programs in ProvinceWest Sulawesi in Indonesia.Conclusion: It is recommended to use the AHP method indetermining the intervention/program BOK utilization of fundsand benefit the most effective and acceptable to all stakeholders.Keywords: Analytic Hierarchy Process, Program BOK